Pengaruh Permainan Tebak Kata Pada Vocabulary Bahasa Inggris - Mega Dwi Susanti (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
The objective of this investigation was to investigate the impact of the word prediction game technique on the growth of English vocabulary in MI NU Assalaam Class 2. The problems studied in this study are 1) How is the influence of the word guessing game method in increasing vocabulary in English subjects in class II MI NU Assalaam Kampungbaru Kepung 2) How do students respond or respond to the application of the word guessing game method in increasing vocabulary in English subjects in class II MI NU Assalaam Kampungbaru Kepung. The sample size of this study was 15 students using the sampling method, namely the total sample. This research uses experimental research methods. Data collection methods include observations, tests, questionnaires, and documents. The results of the study, 1) the average before and after students increased from 66% to 85.33%. The results of the hypothesis test use the t test, and the calculation results are T count and gt; Table T is 10.640 and gt. 2,145 with a significance level of 5%. The results of the analysis showed that the effect of learning using the word game prediction method was significant. 2) According to 75.2% of research results, the use of word guessing games has a significant effect on increasing students' English vocabulary.